Gender Differences in Smoking and Self Reported Indicators of Health - Devichand Pratima; Greaves Lorraine; Kirkland Susan (BMC, 2004)
Abstract Health Issue Smoking among Canadian women is a serious public health issue. Using the 1998-99 National Population Health Survey, this study examined underlying factors contributing to differences in prevalence of smoking among subgroups of women and men, and its effects on self-reported indicators of health. Key Findings In Canada, 26.4% of women and 29.2% of men were classified as current smokers. Higher levels of education and income were associated with decreased odds of current smoking. Adjusting for all other factors, being an ethnic minority decreased the odds of current smoking for both men and women (OR:0.35, 99%CI:0.23-0.54; OR:0.13, 99%CI: 0.09-0.20 respectively). Single mothers had the highest odds of smoking (OR: 2.12, 99%CI: 1.28-3.51) when compared to married mothers with children under 25 years of age. Current women smokers and current and former men smokers were less likely to report very good or excellent health compared with never smokers (OR: 0.83, 99%CI: 0.70-0.98; OR: 0.49, 99%CI: 0.41-0.60; OR: 0.75, 99%CI: 0.63-0.90 respectively). Women who were current smokers had increased odds of needing health care and not receiving it (OR: 1.50, 99%CI: 1.10-2.05). Data Gaps and Recommendations Key issues for Canadian women include an increased prevalence of smoking among young girls and the strong association between smoking and social and economic disadvantage. Tobacco control policies and programs must target high-risk groups more effectively. Of particular importance is the development of programs and policies that do not serve to reinforce existing inequities, but rather, contribute to their amelioration.